Politicizing history of art, breaking free from the absolute origin: Two pending issues - Jaime Vindel (Re-visiones)
Diana Wechsler’s curatorial essay entitled “Images between reality and utopia. Art and history in Argentina” offers a penetrating gaze into two centuries of artistic production in this southern country. In her history, Wechsler reconciles the encompassing whole with the sharpness of each episode that comprises the book of charts with which she invokes Aby Warburg’s figure. Rather than a replication of her approach, the following words refer to provisional answers that —as I consider myself politically a historian— I have reached through my doctoral research of the relations between art and politics in Argentina from the 1960s until the 2001 crisis —two of the moments that Wechsler examines more closely. I do not think I am mistaken if I say that they are possible answers to shared questions. Even on the basis of a general coincidence of our viewpoints, I hope that their presentation will either arouse dialogue or else humbly complement the ideas so solidly expressed in Wechsler’s text.